Monitoramento e supervisão de sensores utilizando aplicação web e API REST - Silva, André Lucas (2019)
This paper presents an enviroment for the collect of sensor readings and information storage in a database accessed by a REST API, that allows the monitoring of the readings with the visualization of the data in JSON format or through reports generated with the help of JasperReports. Due to the different sensor models available in the industry, the entire system is modeled and developed according to scalability and generality requirements.